Potential capacity and cost assessments for hydrogen production from marine sources - Karayel, G. Kubilay; Dincer, Ibrahim (ELSEVIER, 2024)
The current study comprehensively examines the application of wave, tidal and undersea current energy sources of Turkiye for green hydrogen fuel production and its cost analysis. The estimated potential capacity of each city in the country is derived from official data and acceptable assumptions and is subject to discussion and evaluation in the context of a viable hydrogen economy. According to the findings, the potential for green hydrogen generation in Turkiye is projected to be 7.33 million tons using a proton exchange membrane electrolyser (PEMEL). Cities with the highest hydrogen production capacities from marine applications are Mugla, Izmir, Antalya, and Canakkale with 998.10 kt, 840.31 kt, 605.46 kt, and 550.42 kt, respectively. The study calculations obviously show that there is a great potential by using excess power in producing hydrogen which will result in an economic value of 3.83 billion US dollars. This study further helps develop a detailed hydrogen map for every city in Turkiye, using the identified potential capacities of renewable energy sources and the utilization of electrolysers to make green hydrogen by green power. The potentials and specific capacities for every city are also highlighted. Furthermore, the study results are expected to provide clear guidance for government authorities and industries to utilize such a potential of renewable energy for investment and promote clean energy projects by further addressing concerns caused by the usage of carbon-based (fossil fuels dependent) energy options. Moreover, green hydrogen production and utilization in every sector will help achieve the national targets for a net zero economy and cope with international targets to achieve the United Nation's sustainable development goals.
Keywords: Green hydrogen; Wave energy; Tidal energy; Undersea current energy; Cost; Electrolyser; Economy; Environment; Sustainable development; TECHNOLOGIES; Engineering